Dissecting thought patterns: Analyzing how cognitive fragmentation affects conceptualization and problem-solving abilities in junior high school students - Usodo, Budi; Sutopo, Sutopo; Nurhasanah, Farida; Chrisnawati, Henny Ekana; Kuswardi, Yemi; Hendriyanto, Agus (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: This research is rooted in the exploration of a nuanced understanding of the effect of cognitive fragmentation on the conceptual grasp and problem-solving competencies among junior high school students.Aim: The principal aim of this investigation is to delve into the way cognitive fragmentation influences the conceptualization and problem-solving faculties of pupils aged 12-14, from varied academic milieus.Method: Employing a qualitative research blueprint, specifically phenomenological inquiry, the study probes into the subjective experiences and cognitions of the participants. Purposefully chosen for this research, the participants consist of junior high school students. The multi-faceted data collection approach includes task-centered, in-depth individual interviews with students and Focus Group Discussions with educators. The amassed data are then meticulously examined through thematic analysis.Result: Findings of the research reveal diverse manifestations of cognitive fragmentation among the learners. A phenomenon termed 'Pseudo construction' emerges when learners articulate correct responses without wholly comprehending the foundational concepts. 'Mis analogical construction' is recognized when incorrect analogies are deployed in problem-solving, culminating in fallacious solutions. 'Construction holes' are detected when learners exhibit inconsistent responses owing to an absence of alignment with scientific principles.Conclusion: In summation, this inquiry furnishes invaluable insights and evidence-supported strategies to foster efficacious learning and surmount cognitive impediments within the sphere of junior high school education. The conclusions drawn herein contribute to a broader understanding of cognitive dynamics in mathematics education, offering a fresh perspective on enhancing educational practices.